Leveraging conductive inkjet technology to build a scalable and versatile surface for ubiquitous sensing - Gong, Nan-Wei; Hodges, Steve; Paradiso, Joseph A. (Proceedings of the 13th international conference on Ubiquitous computing, 2011)
In this paper we describe the design and implementation of a new versatile, scalable and cost-effective sensate surface. The system is based on a new conductive inkjet technology, which allows capacitive sensor electrodes and different types of RF antennas to be cheaply printed onto a roll of flexible substrate that may be many meters long. By deploying this surface on (or under) a floor it is possible to detect the presence and whereabouts of users through both passive and active capacitive coupling schemes. We have also incorporated GSM and NFC electromagnetic radiation sensing and piezoelectric pressure and vibration detection. We report on a number of experiments which evaluate sensing performance based on a 2.5m x 0.3m hardware test-bed. We describe some potential applications for this technology and highlight a number of improvements we have in mind.